2013
DOI: 10.1002/anie.201303126
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate {W18O56XO6} Clusters with Embedded Redox‐Active Main‐Group Templates as Localized Inner‐Cluster Radicals

Abstract: Polyoxometalates (POMs) [1] are an exceptional family of polynuclear molecular oxide anions usually formed by W, Mo, or V.[2] POMs offer a wide range of structures with diverse physical properties, electronic structures, and applications, such as in catalysis, [3] medicine, [4] materials science, [5] or nanotechnology. Heteropolyoxometalates (HPOMs) are a significant and widely explored subset of POMs. Within this class, the choice of the heteroelement not only determines certain physical properties of the clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Much exploration of POM synthesis and function involves systematic synthesis of series of analogous structures from such systems, incorporating small changes to internally located heteroatoms (e.g., Se in {Se 2 W 29 } units) to alter clusters’ properties. 40 , 41 We propose that, since changes in the heteroatoms do not affect the rigid POM framework structure, comparison of TW CCS N 2 →He values for known structures with different heteroatoms may be substituted in the orthodox IM-MS workflow, replacing comparison with simulated values and allowing the rapid structural assignment of newly discovered POM species.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much exploration of POM synthesis and function involves systematic synthesis of series of analogous structures from such systems, incorporating small changes to internally located heteroatoms (e.g., Se in {Se 2 W 29 } units) to alter clusters’ properties. 40 , 41 We propose that, since changes in the heteroatoms do not affect the rigid POM framework structure, comparison of TW CCS N 2 →He values for known structures with different heteroatoms may be substituted in the orthodox IM-MS workflow, replacing comparison with simulated values and allowing the rapid structural assignment of newly discovered POM species.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, reaction of WO 4 2– and SeO 3 2– salts in acidic aqueous solution is known to produce {Se 2 W 29 } “building blocks”; these form a range of large structures, depending on reaction conditions structures A – C can then be isolated from reaction mixtures (other observed products are smaller). Much exploration of POM synthesis and function involves systematic synthesis of series of analogous structures from such systems, incorporating small changes to internally located heteroatoms (e.g., Se in {Se 2 W 29 } units) to alter clusters’ properties. , We propose that, since changes in the heteroatoms do not affect the rigid POM framework structure, comparison of TW CCS N 2 →He values for known structures with different heteroatoms may be substituted in the orthodox IM-MS workflow, replacing comparison with simulated values and allowing the rapid structural assignment of newly discovered POM species.…”
Section: Results and Discussionmentioning
confidence: 99%
“…With the thermal stability in mind we therefore used a tungsten-based rather than molybdenum-based coreshell cluster. Furthermore, the effect of various dopants was investigated by density functional theory (DFT) calculations, which helped us to understand the likely reactivity and electronic structure of the clusters 13 To provide a first demonstration of a flash memory cell using POMs, a lateral geometry was used with a ,4-nm Si nanowire channel covered with a 4-nm SiO 2 insulator. This design, rather than a vertical flash memory cell, was chosen to provide easy access for the exploration of the intrinsic ability of the POM to form the switching component of a flash memory device (see Fig.…”
mentioning
confidence: 99%
“…The same situation occurs when iodine is the heteroatom in [IW 18 O 62 ] 9À . 34 It has also been observed that in Anderson and Preyssler type anions, not only the M-O-M oxygen atoms but also the X-O-M can be accessed since they present the highest basicity. 35 For example the theoretically calculated basic sites in the decavandate [V 10 O 28 ] 6À anion found in agreement with the crystallographic characterization of [H 3 V 10 O 28 ] 3À .…”
Section: Electronic Structure and Charge Density Of Pom Clusters And ...mentioning
confidence: 99%